The Deinstitutionalization of Lithuanian Mental Health Services in Light of the Evidence-based Practice and Principles of Global Mental Health - Grigaitė, Ugnė (Socialinė teorija, empirija, politika ir praktika, 2017)
During this time, in which Lithuania is going through the deinstitutionalization of its mental health services, the principles of Global Mental Health are especially relevant. This global field for study, research and practice places a priority on improving mental health outcomes as well as reducing respective inequities for all people worldwide. Scaling-up support services for persons who have mental health problems based on both scientific evidence and human rights has become one of the main focuses for action globally, and the key principles of Global Mental Health apply to the situation in Lithuania as much as they do in a number of other countries. This article explores the critical need to effectively reform the existing mental health care system in the country, which in its current form often results in human rights violations. It points to the idea, based on the global evidence base, that different Lithuanian authorities and other key stakeholders could start working together in an intersectoral way in order to reorganize mental health services from institutional to community-based models of care. It is suggested by this article that a sensible, local application of the broad key principles of Global Mental Health could be a mature and rational step taken by Lithuania. This has the potential to be a major step toward the improvement of human rights and mental health outcomes in the country.